(3JMQjQ GdCMcGe aj JOHjQ Cgd GdGSdGes - (3HOQ GdOjf eMeO Hf EHQGgje Hf SYO Gddg Hf LeGYI GdcfGfj,J (B740 (3g` s ((3TeS GdOjf Hf GdTjN MSf Gdchi GdGRgQi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi fYeI GdHGWfI hGdXGgQI hHYO aCMb ef CgOjJ Edjg CgOjJ Gdjg CfhGY GdMce hGdYdhe hhLHJ dg GdfUjMI Ydi GdNUhU hGdYehe s
(3BNQgG (B:s
(3gPg hUjJi Gdjc JYWakG HaVdc YdjfG , hHBNQg OYGA CjVkG JeJ GdhUjI s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3YGQa MceJ s
Keywords: (3eJaQbGJs